Narrativa reflexiva sobre uma experiência individual vivenciada no curso de medicina da Universidade Federal de São Carlos - UFSCar - Guarda, Samira Saad (Universidade Federal de São Carlos, 2024)
This text addresses a reflection on the practice of the Political-Pedagogical Project (PPP) in the Medicine Course at the Federal University of São Carlos (UFSCar) over six years. Initially, an overview of the PPP is presented, highlighting the importance as a strategic guide for educational institutions, aiming to integrate political, pedagogical, and administrative aspects. There is a reflection on the gap between the theoretical expectations of the PPP and the reality experienced during graduation, proposing the need for changes that consider the evolution of society and market demands. The method used consists of continuous reflective narrative throughout the years of graduation. The goal is to analyze the implementation of the PPP in practice and reflect on new perspectives introduced by a reformulation. The spiral is mentioned as part of the PPP, advocating the idea that learning is a continuous and non-linear process. Despite initial difficulties, it is importante to emphasize the benefits of the approach over the years, highlighting the gradual construction of knowledge and its practical application in medicine. The text also addresses criticisms and suggestions for optimization, especially related to time invested in practical activities, visits to health services, communication between students and teachers and evaluation methods.
Reflective narrative about an individual experience lived in the medicine course at the Federal University of São Carlos - UFSCar
Keywords: Projeto Político Pedagógico (PPP); Universidade Federal de São Carlos (UFSCar); Curso de medicina; Prática médica; Ensino médico; Pedagogical Political Project (PPP); Medical course; Medical practice; CIENCIAS BIOLOGICAS